Performance characteristics of a conceptual ring-shaped spar-type VLFS with double-layered perforated-wall breakwater. (May 2019) - Kou, Yufeng; Xiao, Longfei; Tao, Longbin; Peng, Tao
Highlights: Hydrodynamic performance of ring-shaped spar-type VLFS was experimentally evaluated. Long natural periods enhanced vertical motion performance and afforded favorable condition. Large surge damping induced by the breakwater significantly affected the surge and pitch motion. Wave attenuation was frequency-dependent and effective among the common wave frequencies. Wave attenuation and wave run-ups tended to improve in the absence of the leeward walls. Abstract: A ring-shaped spar-type Very Large Floating Structure (VLFS) is proposed as an intermediate base for supporting deepwater resource exploitation far away from the coast line. The proposed VLFS is composed of eight rigidly connected deep-draft spar-type modules and an inside harbor. A double-layered perforated-wall breakwater is vertically attached to the VLFS and pierces through the water surface to attenuate the wave energy in the inside harbor. The hydrodynamic performance characteristics of the ring-shaped VLFS was experimentally evaluated in the present study, focusing on the motion responses, wave elevations, and wave run-ups. The natural periods of the motions in vertical plane were determined to be larger than 40 s, which is much larger than common wave periods. This enhanced the motion performance in vertical plane and afforded favorable habitation and operation condition on the VLFS. A large surge damping was induced by the vertical breakwater, which tended to significantly affect the surge and pitch motions, but had a negligible effect on the heave motion. The component frequencies of the wave elevations in the inside harbor and the wave run-ups were identical with those of the incident waves. The wave attenuation was frequency-dependent and effective for the common wave frequencies, with a smaller loss coefficient observed in higher sea state. The wave attenuation and wave run-ups tended to improve in the absence of the leeward walls.